Autoimmune liver disease following acute hepatitis A infection. Issue 5 (30th May 2019) - Yeend-Curd-Trimble, Hannah; Kelly, Kate; Ghosh, Indrajit; MacDonald, Douglas
Abstract : A male patient in his late 30s presented to our outpatient clinic at Mortimer Market Centre with worsening liver transaminases tests 2 months after a resolved acute hepatitis A infection. A diagnosis of parainfectious autoimmune-like hepatitis phenomena was made based on the history, laboratory and histological features.